Melatonin and blood pressure: a narrative review - О.О. Serhiyenko; V.B. Sehin; V.О. Kuznets; V.О. Serhiyenko (Mìžnarodnij Endokrinologìčnij Žurnal)
Melatonin has several impacts on the cardiovascular system, including the potential to reduce blood pressure in addition to its role in regulating sleep. It has the ability to decrease adrenergic system activity and indirectly enhance endothelial function. Melatonin can provide antihypertensive effects by stimulating own receptors in the central nervous system and peripheral arteries. In addition, melatonin is a potential treatment for patients with hypertension, including the “night-peaker” category. However, the results of only a few randomized trials suggest that melatonin supplements are effective in the treatment of hypertension. Melatonin can lower blood pressure due to vasodilatation, direct blocking of Ca2+ channels and increased production of nitric oxide in the endothelium; antioxidant properties; suppression of the sympathetic nervous system, reduction of norepinephrine production, as well as activation of the parasympathetic nervous system. Because the drug is usually taken at bedtime, it may increase the duration and quality of sleep and therefore lower blood pressure during sleep. Low endogenous melatonin secretion during sleep may be associated with elevated nocturnal blood pressure and comorbid cardiovascular diseases. In addition, melatonin exhibits an excellent safety profile. Consequently, larger-scale, longer-term studies with higher patient heterogeneity, biomarker identification, and idiosyncrasies related to melatonin use are required. The aim of this narrative review is to analyze the peculiarities of the mechanisms of action, as well as the effect of exogenous melatonin on blood pressure parameters in the experiment and clinic. The search was conducted in Scopus, Science Direct (from Elsevier), and PubMed, including the MEDLINE databases. The key words used were “melatonin,” “blood pressure”, “hypertension”, “obesity”, “metabolic syndrome”. We manually searched the bibliography of publications to find study results that the online search did not yield.